OPTIMALISASI PENCEGAHAN DIFTERI PADA BAYI MELALUI PROGRAM IMUNISASI DPT DI LUNG MANE - Zakiyuddin . (Jurnal Pengabdian Masyarakat Multidisiplin, 2019)
Diphtheria cases in the Southeast Asia Region each year rank first in diphtheria cases in the world. This problem can be seen from the position in the Southeast Asia Region since 2000-2015 which always shows the highest number of diphtheria cases in the world. While Indonesia is the country with the second highest incidence of diphtheria compared to other Southeast Asian countries, after India. The reported diphtheria incidence in Indonesia from 2011-2015 was 3,203 cases, while the Indian country was still the country with the highest cases of diphtheria in the world with 18,350 cases of diphtheria. Diphtheria is still endemic in some developing countries even though diphtheria sufferers have dropped dramatically. The number of diphtheria cases in East Java Province still reached 348 cases with a Case Fatality Rate (CFR) of 1.72. The case of diphtheria in Aceh is a case of re-emerging disease because the case of diphtheria has actually declined in 1985, but has increased again in 2017 when there was an outbreak in Aceh Province and tended to increase cases. This service in the form of socialization aims to improve preventive measures or prevent the increase in the prevalence of diphtheria by optimizing the DPT immunization program for mothers who have infants and as health policy makers for the Nagan Raya health service. Kasus difteri di Wilayah Asia Tenggara setiap tahunnya menempati urutan pertama kasus difteri di dunia. Masalah tersebut terlihat dari posisi di Wilayah Asia Tenggara sejak tahun 2000-2015 yang selalu menunjukkan jumlah kasus difteri paling banyak di dunia. Sedangkan Indonesia merupakan negara dengan kasus insiden difteri terbanyak kedua dibandingkan negara di Asia Tenggara lainnya, setelah India. Kejadian difteri yang dilaporkan di Indonesia dari tahun 2011-2015 sebesar 3.203 kasus, sedangkan Negara India masih menjadi negara dengan kasus difteri tertinggi di dunia dengan jumlah kasus difteri sebesar 18.350 kasus. Difteri masih endemik di beberapa negara berkembang meskipun penderita difteri sudah menurun drastis. Jumlah kasus difteri di Provinsi Jawa Timur masih mencapai 348 kasus dengan Case Fatality Rate (CFR) sebesar 1,72. Kasus difteri di Aceh merupakan kasus re-emerging disease karena kasus difteri tersebut sebenarnya sudah menurun pada tahun 1985, namun kembali meningkat pada tahun 2017 saat terjadi KLB di Provinsi Aceh dan cenderung mengalami peningkatan kasus. Pengabdian dalam bentuk Sosialisasi ini bertujuan untuk meningkatkan tindakan preventif atau pencegahan kenaikan tingkat prevalensi penyakit difteri dengan optimalisasi program imunisasi DPT kepada ibu yang memilki bayi dan sebagai penentu kebijakan Kesehatan bagi dinas kesehatan Nagan Raya